2013
DOI: 10.3109/14767058.2013.799658
|View full text |Cite
|
Sign up to set email alerts
|

First trimester maternal lipid levels and serum markers of small- and large-for-gestational age infants

Abstract: PAPP-A was significantly associated with SGA after controlling for confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Parity may also influence neonatal birth weight, and previous studies demonstrated that multiparous women were significantly associated with LGA infants [46,47]. However, another study reported no significant association between parity and SGA or LGA groups [48]. Our study suggests that there is no significant difference in parity among the 3 groups.…”
Section: Discussionsupporting
confidence: 41%
“…Parity may also influence neonatal birth weight, and previous studies demonstrated that multiparous women were significantly associated with LGA infants [46,47]. However, another study reported no significant association between parity and SGA or LGA groups [48]. Our study suggests that there is no significant difference in parity among the 3 groups.…”
Section: Discussionsupporting
confidence: 41%
“…The risk of macrosomia was positively related to TG levels, while negatively related to HDL-C levels in non-diabetic pregnancies [9]. However other studies failed to nd any association [30,31]. In the present study, we found that the incidence of macrosomia was signi cantly increased in the hyperlipidemia group.…”
Section: Discussionsupporting
confidence: 42%
“…Recently, some maternal lipid parameters have been identified as independent risk determinants of fetal overgrowth, especially in pregnancies complicated by GDM or with DM [ 15 , 18 ]. Several studies have demonstrated that in non-diabetic pregnancies, birth weight and the risk of macrosomia or large for gestational age (LGA) were positively associated with maternal serum triglyceride (TG) levels [ 16 , 19 , 20 ], and negatively associated with high-density lipoprotein cholesterol (HDL-C) levels [ 21 ], While other studies failed to find any association [ 22 , 23 ]. Studies have shown that patterns of maternal dyslipidemia and the prevalence of macrosomia vary across populations and ethnic groups [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that in non-diabetic pregnancies, birth weight and the risk of macrosomia or large for gestational age (LGA) were positively associated with maternal serum triglyceride (TG) levels [ 16 , 19 , 20 ], and negatively associated with high-density lipoprotein cholesterol (HDL-C) levels [ 21 ], While other studies failed to find any association [ 22 , 23 ]. Studies have shown that patterns of maternal dyslipidemia and the prevalence of macrosomia vary across populations and ethnic groups [ 23 , 24 ]. While a few studies have explored the relationship between maternal serum lipids and neonatal birth weight in Chinese population, their sample sizes were relatively small [ 21 , 25 ].…”
Section: Introductionmentioning
confidence: 99%